ANALISIS KEBUTUHAN MEDIA E-BOOKLET BERBASIS MINDFULNESS UNTUK MENINGKATKAN KEMAMPUAN REGULASI EMOSI MARAH SISWA - Muthmainnah Amri; Sahril Buchori; Fitriana; Syahril (IKIP Siliwangi, 2026)
This paper aims to analyze the need for developing a mindfulness-based e-booklet as an information tool for guidance services to improve students’ ability to regulate anger at SMP Nasional Makassar. This research was motivated by students’ low ability to recognize, understand, and manage anger adaptively, which impacts impulsive behavior, social interactions, and the learning process. This research uses a descriptive qualitative approach in the form of a needs assessment study, employing data analysis techniques such as in-depth interviews and observations with the research subjects, namely Guidance and Counseling (BK) teachers and two ninth-grade students at SMP Nasional Makassar. The results indicate that most students still struggle to identify emotions, understand triggers of anger, and apply appropriate emotion management strategies. Furthermore, the guidance services provided at the school are still dominated by conventional methods and are not supported by engaging, interactive, and contextual learning materials. Based on these findings, there is a need for engaging, interactive, and contextual guidance media. Mindfulness-based e-booklets are considered a relevant solution because they are designed to assist students in a visual, simple, and easy-to-understand manner, while also encouraging active student engagement in the emotional learning process. These results show that the development of mindfulness-based e-booklets is important as an innovation in guidance and counseling services to support the improvement of junior high school students’ ability to regulate their anger.